2008
DOI: 10.1159/000137628
|View full text |Cite
|
Sign up to set email alerts
|

Oral Vitamin C Supplementation in Hemodialysis Patients and Its Effect on the Plasma Level of Oxidized Ascorbic Acid and Cu/Zn Superoxide Dismutase, an Oxidative Stress Marker

Abstract: Background/Aim: Oxidative stress is known to be enhanced in hemodialysis patients, and one of its useful markers is plasma copper/zinc superoxide dismutase (Cu/Zn-SOD). The increase in plasma Cu/Zn-SOD can be inhibited by orally administered lipid-soluble vitamin E. We examined the antioxidative effects of water-soluble vitamin C administered orally on Cu/Zn-SOD levels in hemodialysis patients. Methods: Vitamin C was orally administered to 16 maintenance hemodialysis patients before each dialysis session. Dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 64 publications
5
25
1
1
Order By: Relevance
“…In the present study, supplementation with a combined vitamins C and E significantly elevated serum vitamin E, consistent with some studies [24][25][26][27], but its results are unlike Hultquist results [23].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, supplementation with a combined vitamins C and E significantly elevated serum vitamin E, consistent with some studies [24][25][26][27], but its results are unlike Hultquist results [23].…”
Section: Discussionsupporting
confidence: 92%
“…SOD serves as an antioxidant enzyme responsible for superoxide removal, and its increase may represent a compensatory response to oxidative stress. 25 The plasma level of the cytosol isoform SOD (Cu/Zn SOD) has been reported as a useful oxidative stress marker in uremic patients in our previous study 26 and in a study by Washio et al 27 In the present study, in patients with CKD, multiple regression analysis was performed on the basis of the results of Spearman rank correlation in all patients with CKD (groups A and B) as well as in a subgroup of patients with CKD and without diabetes (TAbLE 3). The presence of diabetes, Cu/Zn SOD levels, and the percentage of lymphocytes in WBC were found to be significant independent factors affecting plasma CCL23 concentrations in the whole CKD group (r 2 for the model = 0.573).…”
Section: Group B Diabetesmentioning
confidence: 70%
“…A pioneering study by Akiyama et al [81] showed the same effect of these treatments on the expression of the antioxidant enzyme Cu-Zn superoxide dismutase in circulating mononuclear leukocytes of HD patients, which may represent a new in vivo oxidative stress biomarker associated with lipid oxidation of leukocyte plasmalemma [80]. Interestingly, this biomarker does not appear to be affected by the oral supplementation with the hydrosoluble antioxidant vitamin C [94]. This early evidence paves the way to a specific role of vitamin E therapy in the protection of circulating leukocytes, which deserves further clinical investigation in CKD patients on regular HD therapy.…”
Section: Vitamin E-bonded Dialyzersmentioning
confidence: 99%